Assessment of a climate-resilient and low-carbon power supply scenario for Rwanda - Uhorakeye, Théoneste; Möller, Bernd (International Journal of Sustainable Energy Planning and Management, 2018)
<span lang="EN-GB" style="line-height: 102%; font-family: ’Verdana’,sans-serif; font-size: 9pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: FR;">Renewable energy sources are increasingly playing a key role in the transition to a low-carbon based economy while maintaining cost and environmental effectiveness. However, climate change threatens this opportunity especially in countries like Rwanda where the share of hydropower in the total electricity supply mix is high. This study assessed the evolution of Rwanda’s electricity demand towards 2050 and developed a power supply scenario that considers impacts of climate change on the country’s hydropower generation. Based on the findings of the study, it was concluded that the developed scenario is resilient since it meets the projected demand when impacts of climate change are accounted for. Moreover, the scenario ensures the security of the country’s electricity supply because it only relies on domestic energy resources. Furthermore, the suggested scenario positions the country to a low-carbon development pathway compared to the existing power supply plans.